Depoimento especial e escuta especializada: análise da implementação no município de Natal-RN - Lima, Amanda de Medeiros (2020)
This research has as object of study the implementation of law nº 13.431 / 2017, which establishes two methodologies of listening in the child and adolescent protection network, for children and adolescents victims or witnesses of violence: the Special Testimony (ST), which consists of the hearing before court or police authority, and the Specialized Listening (SL) carried out in the other organs of the protection network. Such methodologies seek to avoid secondary victimization of the victim, and have raised concerns among the actors responsible for their execution. Given this scenery, the research aims to analyze the implementation of SL and ST in the city of Natal-RN. In order to subsidize it, the three specific objectives were built: 1. to analyze the actors' conception of ST and SL; 2. investigate how the implementation of the law reverberates in the work of professionals; 3. identify the possibilities and challenges in articulating the network with regard to ST and SL. For this, the study, inspired by historicaldialectical materialism, and using the qualitative methodology was divided into two stages: 1. participant observation during meetings to prepare the service flowchart; 2. conducting eight semi-structured interviews with professionals involved. The data were organized and categorized using the Qualitative Data Analysis Software and subsequently analyzed using the Constant Comparative Method. In this way, it was possible to identify a tension between the professionals of that network, who differ in their conceptions about the proposed law. The lack of training of the actors in the network to deal with the new methodologies, signals another fact that reinforces the challenges faced in the implementation of the legislation, as well as the disciplinary confrontation that is recurrent between the legal sciences and the others. It is expected, therefore, with this investigation to contribute to the work of professionals and, consequently, to be supporting in the protection of children and adolescents.